Peran Pemerintah Dalam Menanggulangi Kerusakan Infrastruktur Jalan Di Desa Bah Tobu Kecamatan Dolok Batu Nanggar Kabupaten Simalungun - Cindy Ayu Lestari; Khoiratul Ummah; Nurul Azmy Pratiwi; Julia Ivanna (Universitas Dehasen Bengkulu, 2023)
The purpose of this study was to see how the Government's Role in Overcoming Damage to Road Infrastructure in Bah Tobu Village, Dolok Batu Nanggar District, Simalungun Regency. The research method used is descriptive research using qualitative methods. The results of this study are that the inhibiting factor in the construction of road infrastructure in Simalungun Regency is the limited budget or available funds, while the development that will be carried out is quite large and extensive with limited budgets available, so the development is not smooth. And also the lack of attention from the Simalungun government and sustainable road maintenance. With road damage such as being able to hamper travel and can cause traffic accidents, it is hoped that the regional government or related agencies will immediately follow up on this matter.